PENGARUH STRUKTUR MODAL DAN MANAJEMEN LABA TERHADAP KINERJA KEUANGAN PERUSAHAAN: Capital Structure, Earnings Management, Company Financial Performance - tuharea, firdaus indrajaya (Fakultas Ekonomi Universitas Gresik, 2021)
This research aims to examine and prove the effect of capital structure and earnings management on the financial performance of companies in large trading sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2019. This research uses a quantitative approach with data analysis methods in the form of descriptive statistics, classical assumption test. , and multiple regression linear analysis. Sampling used the purposive sampling method with a total sample of 13 companies . The results of this study indicate that partially the capital structure has a significant effect on the company's financial performance. While earnings management partially does not significantly affect the company's financial performance. And the capital structure and earnings management simultaneously have no significant effect on the company's financial performance.